Penentuan kandungan nutrien dan antinutrien dalam kernel biji Mangifera pajang Kostermans - Hasnah Haron,; Mamot Said, (penerbit ukm, 2004)
This study was carried out to determine the nutrient and antinutrient contents of the seed kernel of Mangifera pajang Kostermans (bambangan). Proximate analysis for bambangan seed kernel indicated that its nutrient composition was consisted of 38.68% total carbohydrate, 3.08% protein, 4.79% crude fibre, 9.85% total fat, 2.23% total ash and 41.38% water. The kernel also contained 2.04 mg cyanogen glycosides/100 g sample and 0.64% tannin. Oil extracted from bambangan seed kernel showed almost the same physicochemical properties as cocoa butter. The melting point of this oil was at 34.87°C, refractive index at 1.458 and iodine value was 32.97 mg iodine/100 g sample of fat.